Charged particle production in Pb-Pb and p-Pb collisions measured by the ATLAS detector. (January 2016) - Shulga, Evgeny; ,
Abstract: The ATLAS experiment at the Large Hadron Collider measures charged hadron spectra in Pb+Pb and p+Pb collisions. The results are compared to the pp spectra of charged hadrons at the same centre-of-mass energy. Charged hadron distributions from Pb+Pb are compared to charged particle cross-sections in pp collisions at √ s = 2.76 TeV, reference crosssection for p+Pb at √ s NN = 5.02 TeV is reconstructed using √ s = 2.76 TeV and 7 TeV pp results. These allow for a detailed comparison of the collision systems in a wide transverse momentum and rapidity ranges in different centrality intervals. The nuclear modification factors R AA and RpPb are presented as a function of centrality, pT, η The charged particle RAA is found to vary significantly as a function of transverse momentum, and shows a pronounced minimum at about 7 GeV. Above 60 GeV, RAA is consistent with a flat, centrality-dependent, value within the uncertainties. RpPb results show strong rapidity dependence in the region of so-called Cronin peak at about 2 GeV and above pT of 10 GeV show anomalous enhancement.